Architecture and Modern Literature - Spurr, David A. (University of Michigan Press, 2012)
Architecture and Modern Literature explores the representation and interpretation of architectural space in modern literature from the early nineteenth century to the present, with the aim of showing how literary production and architectural construction are related as cultural forms in the historical context of modernity. In addressing this subject, it also examines the larger questions of the relation between literature and architecture and the extent to which these two arts define one another in the social and philosophical contexts of modernity. Architecture and Modern Literature will serve as a foundational introduction to the emerging interdisciplinary study of architecture and literature.